LncRNA DUXAP10 Upregulation and the Hedgehog Pathway Activation Are Critically Involved in Chronic Cadmium Exposure-Induced Cancer Stem Cell-Like Property. (9th August 2021) - Lin, Hsuan-Pei; Wang, Zhishan; Yang, Chengfeng
Abstract: Cadmium (Cd) is a well-known lung carcinogen. However, the mechanism of Cd carcinogenesis remains to be clearly defined. Cd has been shown to act as a weak mutagen, suggesting that it may exert tumorigenic effect through nongenotoxic ways, such as epigenetic mechanisms. Long noncoding RNAs (lncRNAs) refer to RNA molecules that are longer than 200 nucleotides in length but lack protein-coding capacities. Regulation of gene expressions by lncRNAs is considered as one of important epigenetic mechanisms. The goal of this study is to investigate the mechanism of Cd carcinogenesis focusing on the role of lncRNA dysregulations. Cd-induced malignant transformation of human bronchial epithelia BEAS-2B cells was accomplished by a 9-month low-dose Cd (CdCl2, 2.5 µM) exposure. The Cd-exposed cells formed significantly more colonies in soft agar, displayed cancer stem cell (CSC)-like property, and formed tumors in nude mice. Mechanistically, chronic low-dose Cd exposure did not cause significant genotoxic effects but dysregulated lncRNA expressions. Further Q-PCR analysis confirmed the significant upregulation of the oncogenic lncRNA DUXAP10 in Cd-transformed cells. DUXAP10 knockdown in Cd-transformed cells significantly reduced their CSC-like property. Further mechanistic studies showed that the Hedgehog pathway is activated in Cd-transformed cells and inhibition of this pathway reduces Cd-induced CSC-like property. DUXAP10 knockdown caused the Hedgehog pathway inactivation in Cd-transformed cells. Furthermore, Pax6 expression was upregulated in Cd-transformed cells and Pax6 knockdown significantly reduced their DUXAP10 levels and CSC-like property. In summary, these findings suggest that the lncRNA DUXAP10 upregulation may play an important role in Cd carcinogenesis.